A new species of Paspalum, Notata group (Poaceae, Paspaleae), from the Cerrado biome, Brazil: description, chromosome number, and leaf blade anatomy - Oliveira, Regina Célia; Valls, José F.m.; Gomes, Sueli Maria; Fagg, Christopher W.; Pozzobon, Marisa Toniolo (Phytotaxa, 2015)
Paspalum cerradoense R.C. Oliveira & Valls, a new species from the “Chapada dos Veadeiros” region, in the Cerrado biome, Brazil, is here described and illustrated. It is included in the informal Notata group of Paspalum, because of the inflorescences with two distal conjugated racemes. The new species has a chromosome number of 2n=20, which is in agreement with the basic chromosome number of other species of the Notata group. As there are similarities between Paspalum cerradoense, P. cromyorhizon, and P. ionanthum, morphological and anatomical characters of these three species are compared. There are at least 30 differences between these species, which corroborate the consistency of their circumscriptions.